The use of flow cytometry for diagnosis and immunophenotyping in chronic lymphocytic leukemia in a dog: Clinical case report - Sánchez-Solé, Rosina; Pedreira, Graciela; Venzal, José Manuel; Serdio, Paula Pessina; Fonseca-Alves, Carlos Eduardo [UNESP] (ScopeMed, 2022)
Background: Chronic lymphocytic leukemia (CLL) is the most common type of leukemia in dogs. It is characterized by the proliferation of neoplastic lymphocytes in the bone marrow, which are morphologically normal (mature), but non-functional. CLL in canines commonly originates in cytotoxic T lymphocytes (TCD8+), and although there is controversy regarding the prognostic value of the immunophenotype, this cell lineage may be associated with a good prognosis. Case Description: A 10-year-old, entire female, mixed-breed dog was brought to the University Hospital of the Veterinary Faculty (UdelaR) for consultation because a routine pre-surgical check-up revealed lymphocytic leukocytosis, normocytic anemia, and hyperglobulinemia due to an oligoclonal gammopathy. The ultrasound revealed splenomegaly. PCR performed on blood was negative for Ehrlichia canis. Blood and bone marrow flow cytometry was performed to complement the diagnosis and carry out the immunophenotype, which showed CLL of CD8+ T-cell lineage. The clinical suspicion of CLL was confirmed by a myelogram. Chemotherapy treatment based on alkylating agents and glucocorticoids was established. So far, the patient has an overall survival of 13 months with a good response to treatment. Conclusion: The combination of the immunophenotyping test, the myelogram, and the hematological and biochemical profile confirmed the presence of T-CLL in our patient. Flow cytometry, increasingly used in veterinary medicine, allowed us to confirm the diagnosis of CLL originating in cytotoxic T lymphocytes in our patient, through the presence of positive staining of primary antibodies specific for the canine species CD45, CD3, CD5, and CD8 and the absence of staining for CD4, CD21, and CD34.
Keywords: Canine; Chronic leukemia; Cytotoxic T lymphocytes; Immunophenotype; Lymphocytosis